The heretics of finance : conversations with leading practitioners of technical analysis - Lo, Andrew W. (Andrew Wen-Chuan) (Bloomberg., 2009)
"An exploration of the evolution and practice of technical analysis with thirteen of the industry's top practitioners"--Provided by publisher.